Monday

April 21, 2014

April 21, 2014

Posted by **Abbey** on Tuesday, April 13, 2010 at 7:17pm.

k(2k+1) +(4(k+1)-1) = (k+1)(2(k+1)+1)

k^2+2k+3 For the right side?

- Math -
**Reiny**, Tuesday, April 13, 2010 at 7:20pmLS = k(2k+1) +(4(k+1)-1)

= 2k^2 + k + 4k + 4 - 1

= 2k^2 + 5k + 3

RS = (k+1)(2(k+1)+1)

= (k+1)(2k+2+1)

= (k+1)(2k+3)

= 2k^2 + 5k + 3

mmmhh?

- Math -
**Abbey**, Tuesday, April 13, 2010 at 9:10pmThank you!

**Related Questions**

Math - I need to show that the right side equals the left side but I am having a...

Trig - Proving Identities: 2 columns (tan + cot)^2 = sec^2 + csc^2 I'm having ...

Physics - A 60.9 kg climber is using a rope to cross between two peaks of a ...

Trig - The question is: Set up a 2 column proof to show that each of the ...

Math - Hello, Having trouble with this one... Solve the inequality: (2x-3)(4x)+x...

Math - Cross multiplication means that you multiply? the numerator on the left ...

chem again - One more question- how do I balance this half-reaction in terms of ...

geometry - Right triangle ABC is similar to triangle XYZ, because angle B is ...

geometry - Right triangle ABC is similar to triangle XYZ, because angle B is ...

proof by mathematical induction - subject is PreCalulus. 2^(k+3) = and < (k+3...